Dinâmica molecular no estudo do ponto de fusão - Farinas, Pedro Sanchez (Universidade Federal de São Carlos, 2023)
The phenomenon of phase transitions is by itself an extremely intriguing phenomenon, and is a central object of investigation in several areas of science. Melting is a first-order phase transition that is present in many situations, and its study has numerous applications in industry (in the oil industry, for example, to avoid the crystallization of its components during extraction and transport processes), in everyday life (as to avoid ice formation on asphalt) and environmental (study of melting polar ice caps fields). In particular, it is of interest in chemistry to study the melting point of crystals whose constituents are organic compounds (molecular crystals), since these crystals can be manipulated for application in organic syntheses and other laboratory applications. This work brings a review of several concepts involved in the study of the melting point of molecular crystals, focusing on crystals formed by hydrocarbons with not very long chains. The objective is to explain the importance of computational studies on the subject, correlating with experimental studies and bringing some difficulties and results, with emphasis on the even-odd effect and its microscopic origins, which are difficult to investigate experimentally, and on the molecular dynamics method to simulations of the fusion of molecular crystals. In Chapter 1, general aspects of phase transitions are discussed, in Chapter 2 the objectives of this work are presented and in Chapter 3 the discussion is focused in solid −→ liquid phase transition (melting), with emphasis on how this transition occurs in organic compounds and reviewing the even-odd effect. In the Chapter 4, a review of fundamental aspects of molecular dynamics simulations is made, and in Chapter 5, the application of molecular dynamics in the study of the melting point of molecular crystals is discussed, highlighting some techniques applied to improve the method and some results from the literature.
Molecular dynamics in the study of the melting point
Keywords: Ponto de fusão; Transição de fase; Simulação de dinâmica molecular; Química computacional; Hidrocarbonetos; Melting point; Phase transition; Molecular dynamics simulations; Computational chemistry; Hydrocarbons; CIENCIAS EXATAS E DA TERRA::QUIMICA